Isolation and Characterization of Exopolysaccharide Produced by Tributyltin Chloride Degrading Marine Bacterium Alcaligenes sp. 2-6 Strain S3 from Goa, India: Characterization and Applications of Exopolysaccharide Produced by TBTC Degrading Marine Bacterium (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The aim of the study was to isolate and characterize the Exopolysaccharide (EPS) produced by Tributyltin Chloride (TBTC) degrading marine bacterial isolate under TBTC stress from Goa, India. A highly potent TBTC degrading marine bacterial isolate was isolated and identified to be Alcaligenes sp. 2-6 strain S3 using morphological, biochemical and molecular characteristics (16S rDNA Sequence taxonomic phenogram). The isolate grew and produced 98.3µgmL EPS in Zobell marine broth (ZMB) and 46.8µgmL in Mineral salts medium (MSM) supplemented with 5mM TBTC. The exopolysaccharide was extracted and chemically analysed following standard procedures, which revealed its acidic nature and the presence of neutral sugars, proteins, uronic acids and methyl pentoses. The Fourier transformed infrared (FTIR) spectroscopic scan revealed the presence of functional groups as hydroxyl, carboxylic and amides, corresponding to acidic hetero-polymeric polysaccharide, possessing good emulsification activity. A highly potent TBTC degrading marine bacterium was isolated and identified as Alcaligenes sp. 2-6 strain S3, which produced more EPS in ZMB than in MSM under TBTC stress. The EPS was chemically analysed and the FTIR spectrum revealed it to be an acidic heteropolysaccharide, with good emusifying activity. This is the first report of EPS production and characterization by TBTC degrading marine bacterium Alcaligenes sp. 2-6 strain S3, which significantly contributes towards an understanding of the chemical composition and applications of the EPS in environmental bioremediation of TBTC contaminated sites of Goa, in India.